Emerging Views of Kinships Created Through Oocyte Donation. Issue 1 (January 2020) - Hershberger, Patricia E.; Driessnack, Martha; Kavanaugh, Karen; Klock, Susan C.
Abstract: Background: The United States has the highest number of oocyte donation cycles, which account for an estimated one-quarter of all worldwide oocyte donation cycles. Although there has been a steady rise in oocyte donation treatment, understanding the kinship views of those intimately involved is lacking. These include women oocyte donors and parents who received donor oocytes to establish a pregnancy. Purpose: To explore the views and perspectives about genetic relationships and lineages among women who were oocyte donors and parents who received donated oocytes 10 to 12 years after donors and parents underwent oocyte donation procedures to establish a pregnancy. Study Design and Methods: A longitudinal cohort of pregnant women who received donor oocytes participated in an expanded, follow-up study 12 years postpregnancy that included the women's heterosexual partners and biological fathers. Women who donated oocytes anonymously 10 to 12 years prior also participated. Qualitative content analysis was used to analyze participants' in-depth interviews. Results: Six women who received donor oocytes and their heterosexual partners and biological fathers ( n = 6), representing 12 children conceived by oocyte donation, and 3 women who donated oocytes anonymously representing 3 children participated. Themes that emerged from the women oocyte donors included a reexamination of anonymity and contact with recipient families, managing disclosure to their own children about possible half-siblings, and potential for consanguinity. For recipient parents, there was an overwhelming sense of gratitude to the women oocyte donors, concerns about navigating genetic information gaps, and contemplating future contact with the donors and/or half-siblings. Clinical Implications: Nurses can play a vital role in supporting and educating women oocyte donors and recipient parents about navigating complex relationship issues in donor kinships. Abstract : The United States has the highest number of oocyte donation cycles, which account for an estimated one quarter of those worldwide. There is minimal evidence to support understanding of kinship views of those intimately involved. In this study, women who were donor oocyte recipients and their partners, as well as women who were oocyte donors, were interviewed 10 to 12 years after the procedure.